Primates on display: Potential disease consequences beyond bushmeat. (20th January 2017) - Muehlenbein, Michael P.
Abstract: Human interactions with nonhuman primates vary tremendously, from daily cultural engagements and food commodities, to pet ownership and tourist encounters. These interactions provide opportunities for the exchange of pathogenic organisms (both zoonoses and anthroponoses). As exposures are not limited to areas where bushmeat usage continues to be a major problem, we must work to understand better our motivations for engaging in activities like owning primates as pets and having direct physical contact with wild primates within the context of nature‐based tourism. These topics, and the theoretical potential for pathogen transmission, are reviewed in the present manuscript. This is followed by a case study utilizing 3845 survey responses collected from four international locations known for primate‐based tourism, with results indicating that while a majority of people understand that they can give/get diseases to/from wild primates, a surprising percentage would still touch or feed these animals if given the opportunity. Many people still choose to touch and/or own primates, as their drive to bond with animals outweighs some basic health behaviors. Desires to tame, control, or otherwise establish emotional connections with other species, combined with the central role of touch for exploring our environment, necessitate the development of better communication and educational campaigns to minimize risks of emerging infectious diseases.